Laparoscopic Surgery in Gynaecology - Attiya Begum,Rubina Ashraf,Rubaba Abid,Fehmida Shaheen (Journal of Rawalpindi Medical College, 2015)
Background: With the advent of technological advancements, the indications for gynecological laparoscopy are increasing. We evaluated the results of our experiences with gynaecological laparoscopies and assessed rate, indications, complications and benefits in a teaching hospital. Methods: In this retrospective observational study, a total of 137 patients had laparoscopic procedure done during the period January 2011 to December 2014 and were included in the study. Laparoscopic surgeries were performed under general anesthesia. Successful creation of the pneumoperitoneum was created with the help of Veress needle, mostly by closed access technique and occasionally with the open method. Secondary ports were introduced under direct vision. After completing the surgery laparoscope and secondary ports were removed under direct vision to minimize any iatrogenic insult. Results: During the study period, 874 major gynaecological operations and 137 laparoscopies were performed. This gave the rate of 15.6% laparoscopies per 100 operations. Diagnostic laparoscopies were 48 (35%), operative were 89 (65%) and 8 (5.8%) laparoscopies were converted into open surgery due to technical difficulties. Complications were 8 (5.8%), majority being of minor nature except one major complication being a bladder injury. Conclusion: Laparoscopic surgery offers unique benefits. These are establishing definite diagnosis, mobilization and speedy recovery, minimal complications, less cost and shorter hospital stay. In young patients, laparoscopy helps in preserving their fertility with better prognosis in contrast to open surgery.